PENDIDIKAN LINGKUNGAN BERBASIS EKOLOGI INTEGRAL DAN IMPLEMENTASINYA DALAM DUNIA PENDIDIKAN - Andini, Riddo; rahmanita, rahmanita (Mau`izhah : Jurnal Kajian Keislaman, 2023)
The aim of this research is to introduce integral ecology-based environmental education which is applied in formal learning at school. This research uses library research, with a postpositivisme phenomenologik-interpretif approach. The results of this research study include: Ecological education learning materials and strategies, Implementation of Integral Ecology in the World of Integral Ecology-Based Education. In implementing ecology, it is providing teaching and learning in every education. Which aims to shape humans to have moral and moral responsibility and full awareness of their nature as humans. On the other hand, every problem of integrating Islamic education in ecology has a solution to every problem in order to achieve the ecological goals of Islamic education.